Choral speaking for the elementary fast learners - Santos, Bayani J. 1934- (1967)
This study tested the effectiveness of choric speaking as a method of teaching. It determined the objectives and guiding principles of choral speaking and personal development that students acquire through participation in a verse speaking choir, and the method by which choral speaking can be effectively taught to children.
Thesis (M.A.T. Special Education)--University of the Philippines, Diliman.
Keywords: Choral speaking